Effectiveness of an Education Program on Primary School Teachers Knowledge towards T1DM - Aqil Jaber Abd Al-Hamza, Sawsan Ali Mahmood, Khamees Bandar Obaid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Schools have an important role to play in ensuring that students with diabetes have the support they need to stay healthy, enjoy the same opportunities for learning and having fun as their peers, and are prepared to do their best in school. Training teachers and education professionals on diabetes is crucial for full-time monitoring of diabetic children in schools. The aims of study is to evaluate the effectiveness of an intervention program on teachers knowledge towards management of students with type I diabetes mellitus. Methods: A quasi-experimental study conducted on a group of teachers in the Numaniyah district using the pre and post assessment. Using an purposive sample of 60 teachers divided into two groups of 30 samples for each them. The educational program was conducted on 30 teachers and they were compared to the control group. The reliability of the questionnaire was achieved through a pilot study and then presented to experts to prove its validity. The total number of items included in the questionnaire was 30-items. The data was collected by using the self-report method and analyzed by applying a descriptive and inferential statistical data analysis approach. Results: The results of the study indicated that the (70%) of school teachers expressed deficit knowledge, and after the application of intervention program, (66.7%) of school teachers expressed good knowledge. While in the control group for two tests, the teachers’ knowledge was poor (86.7% and 76.7%) respectively. There is a no statistical significant difference between intervention and control groups in the pre-test period of measurement (p=0.230). While, there is a highly statistical significant difference between the intervention and control groups at the post-test period of measurement (p=0.000). Conclusions: Training the primary school teacher’s staff by the implementation such education program which indeed helps to develop their knowledge. Ministry of Health and Education should try to consider teachers benefits. It should adjust training on managing diabetes at school program’ aims to increase the awareness of the teachers on diabetes. Increase the awareness of childhood diabetes, it is critical to expand the management strategies to every area, other than healthcare institutions, to which children attend.